Makanan Sehat untuk Mencegah Dismenore dan Anemia pada Remaja Putri di Pondok Pesantren As’ad Kota Jambi - Iin Indrawati; Siti Fati Hatussaadah; Aisah Aisah; Maryam Novitasari; Hesty Hesty (Prosiding Seminar Kesehatan Nasional, 2025)
Lack of iron intake can cause anemia in adolescents. Adolescent girls are at higher risk of developing anemia due to their physical growth, reproductive maturation, and cognitive transformation, which require high iron requirements. Some adolescent girls reported experiencing menstrual pain, one had not yet menstruated, and another looked pale. This condition is feared to impact the health of adolescent girls, especially their reproductive system, in the future. If an adolescent suffers from anemia, she will usually experience dysmenorrhea during menstruation. The purpose of this activity is to increase adolescent girls' knowledge of the importance of consuming healthy foods to prevent dysmenorrhea and anemia. The lack of adequate nutrition for the body during a period of rapid growth and development, along with the impacts that will occur on adolescent girls, is one of the reasons for the author to take preventive measures in the form of Health Education with the theme Healthy food to prevent dysmenorrhea and anemia in adolescent girls at the As'ad Islamic Boarding School in Jambi City. The activity was carried out face-to-face with participants, aiming to increase adolescent girls' knowledge about the importance of healthy and appropriate foods for adolescent girls to prevent dysmenorrhea and anemia. The results showed an increase in the knowledge of young women with an increase in the average score of 37.5 from the average pre-test score of 32.4 to an average post-test score of 70. The activity was carried out for 6 months from March to August 2024 at the As'ad Islamic Boarding School in Jambi City.